Sosialisasi Budaya Menabung Melalui Platform Dinaran - Riski, Bagus; Setiawan, Adil; Ridwan, Muhammad; Ananda, Dea; Syahputra, Firman; Aulia, Novi (LPPM Universitas Potensi Utama, 2024)
Islamic This community service program aims to socialize the importance of a saving culture to the students of BLK Darul Musthofa using the digital platform Dinaran. The Dinaran platform, designed to facilitate the saving process with advanced digital features, is introduced as an effective tool in forming sustainable saving habits. The socialization activities include seminars and training that provide in-depth understanding of personal financial management and the benefits of saving. By using the Dinaran platform, participants are taught how to create savings plans, monitor expenses, and leverage technology to achieve their financial goals. Gold is an instrument that can protect wealth due to its inflation-resistant nature compared to paper money. The community service activities held at the Darul Musthofa Vocational Training Center (BLK), specifically attended by the students of BLK Darul Musthofa, provide the younger generation with the opportunity to understand the importance of saving from an early age. In these activities, the community is also introduced to the concept of saving in gold through the Dinaran platform. Saving in the form of gold has various advantages, such as protection against asset value from inflation and economic fluctuations. The Dinaran platform provides convenience for the community to buy, store, and manage gold digitally, making gold investment more accessible and safe. Students are taught how to use the Dinaran platform to buy gold in small amounts regularly, enabling them to start saving with affordable capital. Additionally, through this platform, they can monitor the value of their investments in real-time and sell their gold whenever needed. This offers greater flexibility and accessibility compared to traditional methods of storing physical gold. In this socialization, practitioners or lecturers provide insights into the history and market trends of gold, as well as effective investment strategies. They also discuss potential risks and how to manage them. Thus, participants gain a comprehensive understanding of saving in gold and how to utilize it to achieve long-term financial stability. Although the activities mainly involve students, it is hoped that the students will also share the information with their parents and the community. This aims to create collective awareness about the importance of saving and investing culture. With collaboration between students, parents, and the community, it is expected that the saving culture can be implemented comprehensively and sustainably. This program is expected to increase public awareness of the importance of saving and provide them with the necessary knowledge to manage their finances better in the digital era. By saving through the Dinaran platform, students are expected to achieve better financial security and more effective wealth protection through digital gold saving.